The application of ultrasonic nebulization to ICP-AES analysis of metallurgical and geological samples - Barnardt, C. A. (Cornelius Andries) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 1987.